Seni Menurut Perspektif Hazrat Inayat Khan dan Sayyed Hossein Nasr - Edi Sumanto (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2021)
This paper seeks to see and compare the opinions of Hazrat Inayat Khan and Sayyed Hosseini Nasr regarding art. The method used in this paper is qualitative and the data sources used are literature, both books and journals. Hazrat Inayat Khan argues that art is what humans create, and nature is what God creates. The point is that art is a creation of humans, whose creations can be seen or heard. One of the creations seen, for example, is painting. Whereas what is heard is like music. Then nature is what God created such as mountains, rivers and so on. But humans are also creations of God. The Art Opinion, stated by Sayyed Husien Nasr, describes religious values, so that there is no such thing as secular art. So that there are no restrictions between religious and secular in the world of Islamic society. Explaining the spiritual qualities that are characterized by polite procedures due to the impact of Sufism values various kinds of art.